2007
DOI: 10.1021/ac701626y
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic Detection of Bacterial Genomic DNA Using the Bio Bar Code Assay

Abstract: The detection of bacterial genomic DNA through a non-enzymatic nanomaterials based amplification method, the bio-barcode assay, is reported. The assay utilizes oligonucleotide functionalized magnetic microparticles to capture the target of interest from the sample. A critical step in the new assay involves the use of blocking oligonucleotides during heat denaturation of the double stranded DNA. These blockers bind to specific regions of the target DNA upon cooling, and prevent the duplex DNA from re-hybridizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(74 citation statements)
references
References 42 publications
0
74
0
Order By: Relevance
“…At pH 7.0, the linear range of the H 2 O 2 sensor was from 0.5 to 115 mm, with a correlation coefficient of 0.9988 (inset in Figure 7), which is much wider than that (from 5 to 45 mm) of a reported biosensor. [40] The detection limit with a signal-to-noise ratio of three was estimated to be 0.12 mm, which is lower than the level of 1.4 mm reported for a (PDDA/Fe 3 O 4 NPs) 5 multilayer modified electrode. [41] For comparison, the amperometric responses of l-HCNTs/GCE and MWCNTs/ GCE are shown in Figure 7(curves b and c).…”
Section: More Importantly We Compared the Catalytic Efficiencies Of mentioning
confidence: 59%
“…At pH 7.0, the linear range of the H 2 O 2 sensor was from 0.5 to 115 mm, with a correlation coefficient of 0.9988 (inset in Figure 7), which is much wider than that (from 5 to 45 mm) of a reported biosensor. [40] The detection limit with a signal-to-noise ratio of three was estimated to be 0.12 mm, which is lower than the level of 1.4 mm reported for a (PDDA/Fe 3 O 4 NPs) 5 multilayer modified electrode. [41] For comparison, the amperometric responses of l-HCNTs/GCE and MWCNTs/ GCE are shown in Figure 7(curves b and c).…”
Section: More Importantly We Compared the Catalytic Efficiencies Of mentioning
confidence: 59%
“…Protein-inorganic surface interactions have gained increasing attention owing to their widespread occurrence in nature, and their broad range of applications in nanobiotechnology (Choi et al 2009;Hill et al 2007;Hu et al 2005;Jackson et al 2000;Laera et al 2011;Manecka et al 2014;Millo et al 2009;Park et al 2008;Qin et al 2007a, b;Slocik et al 2011;Xu et al 2010). Adhesion of proteins on solid substrates is utilized by many organisms, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, it was found that the K m value of CuFe 2 o 4 /gQDs with TMB as substrate was 3.3 times lower than that of HRP reported in the previous paper by comparing the apparent kinetic parameters [52], indicating that CuFe 2 o 4 / GQDs have a higher reactivity to TMB than HRP. Additionally, the K m value of CuFe 2 o 4 /gQDs with H 2 o 2 as substrate was 2 times lower than that of HRP and the other peroxides nanomimetics reported recently [53], suggesting that CuFe 2 o 4 /gQDs have a higher reactivity to H 2 o 2 than HRP and other nanomaterials. This might be because of the advantages of CuFe 2 o 4 /gQDs globular structures and quantum properties such as the larger specific surface area, stronger absortion ability, higher conductivity and dispersion for TMB and H 2 o 2 as substrates, which would provided a lot of practice sites of reaction and expanded contact areas of reaction, effectively improving the efficiency of the reaction.…”
Section: Kinetic Assay Of the Cufe2o4/gqds Mnpsmentioning
confidence: 56%